REAKSI INVESTOR ATAS CORPORATE GOVERNANCE PERCEPTION INDEX (CGPI) 2011 - Makaryanawati Makaryanawati (University of Merdeka Malang, 2012)
The objective of this study was to determine the capital market reaction on the announcement of CorporateGovernance Perception Index (CGPI) 2011. The variables used in this study were stock prices over the closingprice and trading volume of shares. The type of analysis was comparative descriptive study which comparedthe stock price and trading volume before and after the CGPI 2011 award-winning announcement for thecompanies listed in IDX. Observations were made during the period of 10 trading days; five days before andfive days after the CGPI 2011 announcement. The data analysis instrument used in this study was the WilcoxonSigned Ranks Test with significance level = 5%. The results showed that there was no difference betweenstock prices before and after the announcement of CGPI 2011, there were differences in the trading volumeactivity before and after announcement of CGPI 2011 at the companies of CGPI 2011 winners that were listedin IDX. Based on these results, it could be concluded that stock price of the sample companies could not beaffected by the information content of CGPI 2011 because the sample companies were fundamentally strongcompanies. The award announcement could affect the shares trading volume in the capital market.